Marriage legalization: Preserving the customary marriage tradition of the ethnic Chinese community in Cirebon City - Gusti Yosi Andri; Aris Putra Nandar; Bambang Wibisono; Dharliana Hardjowikarto; Eni Suhaeni; Raymond Angwarmase; Murtiningsih Kartini (Interdisciplinary Social Studies, 2024)
This study aims to investigate efforts to preserve traditional Chinese marriages through marriage legalization in the city of Cirebon, Indonesia. The study used a qualitative approach with a descriptive type of research because it is to minimize changes in attitudes from the millennial generation that can cause the loss of traditions and cultural heritage of ancestors regarding customary marriage. The population studied was ethnic Chinese who are members of the Chinese Ethnic Social Clan, both traditionally and nationally. Data analysis was carried out using the content analysis method, using concepts from structural functionalism theory and social change theory as the framework of analysis. The results of the research show that marriages that are not registered can still be submitted for registration, even though they have exceeded the maximum limit (60 days) as long as a court decision in the form of a determination of marriage registration is obtained first. The validity of marriage is also studied from the theory of structural functionalalism. This research contributes to preserving cultural heritage by addressing the legal recognition of customarily married marriage in the Chinese ethnic community. The government needs to issue provisions that regulate the issue of the marriage registration mechanism due to the delay in marriage registration so that couples who have been married and have not been recorded get legal certainty that protects the validity of their marriage, especially regarding the status of children.